Penerapan Pijat Oksitosin untuk Memperlancar Asi pada Pasien Post Sc di Ruang Alamanda RSI PKU Muhamadiyah Pekajangan - Pitriasih Handayani; Nuzulia Fitriani; Iskandar yusuf; Shisca Octavia Maharani; Yuliati, Yuliati; Wahyuningsih, Wahyuningsih (Journal of Medical Practice and Research, 2026)
This empirical descriptive case study explored the implementation of oxytocin massage to improve breast milk flow among post–Sectio Caesarea mothers in the Alamanda Ward of RSI PKU Muhammadiyah Pekajangan. Five participants were selected through purposive sampling based on predefined inclusion and exclusion criteria. Data were collected using structured observation sheets assessing lactation indicators, clinical responses, and implementation quality over three consecutive days. Findings indicate that oxytocin massage was associated with progressive stabilization of postoperative physiological conditions, enhanced maternal readiness for breastfeeding, and consistent clinical implementation aligned with institutional standard operating procedures. The integration of structured monitoring and complete documentation supported reliable evaluation of lactation outcomes within the case-study framework. The results highlight that effective implementation quality plays a crucial role in maximizing the neurohormonal mechanisms underlying milk ejection reflexes in post-surgical mothers. These findings support the incorporation of oxytocin massage as an evidence-informed, non-pharmacological nursing intervention to optimize lactation management in post–Sectio Caesarea care settings.